Dataset on electro-optically tunable smart-supercapacitors based on oxygen-excess nanograin tungsten oxide thin film - Akbar I. Inamdar; Jongmin Kim; Yongcheol Jo; Hyeonseok Woo; Sangeun Cho; Sambhaji M. Pawar; Seongwoo Lee; Jayavant L. Gunjakar; Yuljae Cho; Bo Hou; Seung Nam Cha; Jungwon Kwak; et al. (Data in Brief, 2017)
The dataset presented here is related to the research article entitled “Highly Efficient Electro-optically Tunable Smart-supercapacitors Using an Oxygen-excess Nanograin Tungsten Oxide Thin Film” (Akbar et al., 2017) [9] where we have presented a nanograin WO3 film as a bifunctional electrode for smart supercapacitor devices. In this article we provide additional information concerning nanograin tungsten oxide thin films such as atomic force microscopy, Raman spectroscopy, and X-ray diffraction spectroscopy. Moreover, their electrochemical properties such as cyclic voltammetry, electrochemical supercapacitor properties, and electrochromic properties including coloration efficiency, optical modulation and electrochemical impedance spectroscopy are presented.